Answer:
Step-by-step explanation:
1st one is x=26
2nd one is x=4
3rd is x=4
4th is x=-1
Hope that helps!
Answer:
x = -8
y = 9
Step-by-step explanation:
to solve this expression using simultaneous equation, we would say let
y =9............................................. equation 1
6x + 5y =-3............................................equation 2
substitute equation 1 into equation 2
-3 = 6x + 5y............................................equation 2
6x + 5(9) = -3
6x + 45 = -3
collect the like terms
6x = -3-45
6x = -48
divide both sides by the coefficient of x which is 6
6x/6 = -48/6
x = -8
therefore y = 9
x = -8
Answer:
Hi I need to get another chance to go back to school subject1
Answer:
9/4 cubic feet
Step-by-step explanation:
1.5*3/4*2=9/4
Answer:
x=-3
Step-by-step explanation:
-2x2=-4
-4-16x-44=0
combine like terms (-4,-16)
-48-16x=0
move the 16x to the other side of the equal sign (add 16 since its -)
-48=16x
you need x alone so you need to divide by 16
-3=x